Oral Cancer Awareness And Practice Of Risk Habits And Mouth Self-Examination In High Risk Indigenous Community In Sarawak, Malaysia - Maling, Thaddius Herman; Doss, Jennifer Geraldine; Yun, Low Wah (IIUM Medical Journal Malaysia, 2017)
Introduction: This study was to obtain baseline information and its associated factors on oral cancer awareness, practice of risk habits and mouth self-examination (MSE) among selected highrisk indigenous community in Sarawak. Materials and Methods: Cross-sectional survey using faceto-face interview was conducted on consented Malaysian, aged ≥15 years old who attended a one day Ministry of Health annual oral cancer screening programme at Bisaya villages in Limbang, Sarawak. Data were analysed using chi-square and multiple logistic regression. Significance level was set at p<0.05. Results: 75.1% of respondents were aware of oral cancer. Smoking was the most recognised risk habits (85.1%). About three-quarter of respondents recognised non-healing ulcer (74.7%) and red/white spot (72.1%) in the mouth as possible early cancer signs. Men had higher prevalence of smoking (85.7%) and drinking (70.8%)(p<0.01), whereas, women had higher percentage of betel quid chewing (62.5%). Low income was significantly associated with smoking and alcohol habits, whereas older age group and lower education level were significantly associated with betel quid chewing. Although 94.8% of respondents agreed that early detection may improve treatment outcome, only 33.8% had heard about MSE. Respondents who ever heard of MSE were 57 times more likely to practice MSE. Conclusion(s): Majority of selected high-risk indigenous community were aware of oral cancer, however awareness of MSE are still lacking. Gender, age, education level and income were significantly associated with health-risk behaviours. Future health promotion agenda should focus in addressing socio-environment gaps, and develop health education intervention based on specific health behaviour theory.